General Formula for Calculation of Dimensions and Surfaces of Some Geometric Figures - Bozorov Zokir Yuldosh oglu; Khabibulloyev Abbos Odil oglu; Turakhanov Jakhongir; Otaganova Umida Egamberdi qizi (International Journal on Orange Technologies, 2022)
In this paper, the general formula for calculating the volumes and surfaces of some geometric figures is revealed based on the application of Simpson's formula in calculating the volume of spatial objects and the faces of some planametric shapes.